Analisis Distribusi Suhu Aksial Teras Dan Penentuan keff PLTN Pebble Bed Modular Reactor (PMBR) 10 MWE Menggunakan Metode MCNP 5 - Setiyo, Agung; Munir, Mohamad (BERKALA FISIKA, 2010)
The axial temperature distribution and effective multiplication factor (Keff) for PBMR 10 MWe which used uranium dioxside (UO2) as fuel, graphite as moderator, and helium (He) gas as cooler with heterogenous reactor design which used geometry of reactor core finite cylinder has been investigated. The axial temperature distribution of reactor core analysized by splitting core reactor become 57 layers axially and every layer has height 14,9 cm. Keff of reactor Â calculated by MCNP 5 with fuel enrichment variation from 7 to 10% and variation range 0,5%. The result shows that reactor in critical condition with fuel enrichment 8,6% and average temperature of reactor core is 893,635 K. Â Keywords: PBMR, MCNP, Temperature distribution, Keff